CLINICAL PROFILE OF ADOLESCENT GIRLS WITH GYNAECOLOGICAL PROBLEMS IN RURAL SOUTH INDIA - VANI, NULAKATHATI; SRAVANI, NISHADHAM; RAMYA, THIPPESWAMY; RATHINAVELU, MOHANRAJ; SUCHITRA, MEKALA JYOTHI (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: The purpose of the six months observational study is to evaluate the gynaecological problems of the adolescent girls, attending the gynaecological outpatient department of a secondary care referral healthcare facility in rural south India. Methods: After ethical clearance, adolescent girls in the age group of 10-19 y having gynaecological problems, who had experienced at least 3 consecutive menstrual cycles, and who showed willingness towards study were included; and adolescent girls in 10-19 y age group having a pregnancy and its complications were excluded. Results: Out of 161 adolescent girls, 46.01% belong to late adolescence with more distribution of gynaecological problems. The gynaecological problems majorly observed were menstrual disorder 59.63%, abdominal pain (11.18%), white discharge per vagina (9.94%), and 8.07% of heavy menstrual bleeding. The menstrual disorder complained with amenorrhea 40.63%, polymenorrhea 18.75%, and menorrhagia 16.67%. In our study, 26.09% and 32.3% of adolescent girls were anaemic and underweight, respectively. Conclusion: In conclusion, our study showcased evidently that young adolescent girls are at higher risk of both gynaecological problems and menses disorders in the rural setting; for whom more amount of awareness to be parented and education of menstrual hygiene and hemodynamic effects has to be culminated through health education, for a future healthier nation.